Hydrochemical evolution and groundwater quality assessment of the Tinejdad-Touroug quaternary aquifer, South-East Morocco - Ait Said, Brahim; Mili, El-Mostafa; El Faleh, El Mati; Mehdaoui, Radouan; Mahboub, Abderrahmane; Hamid, Fatima Ezzahra; Tlemcani, Jihane; El Fakir, Rabia (Frontiers in Ecology and Evolution, 2023)
The Palm Grove ecosystems situated in the southeastern region of Morocco are highly vulnerable to compromise, encountering significant challenges due to insufficient precipitation and limited availability of groundwater. The objective of this study is to evaluate the groundwater quality of the Tinejdad-Touroug aquifer for domestic and irrigation purposes. Groundwater flows from southwest to northeast mostly in Quaternary conglomerate-lacustrine facies in the Rheris basin. The results show that the domination of the major ions is in the following order: Cl->HCO3->SO42->Na+>Ca2+>Mg2+> NO3->K+>NO2->NH4+. Piper diagram showed the predominance of a single mixed chemical facies Cl-SO4-Ca-Mg, as well as the presence of exceptions of some samples that showed other facies variations. The water quality index assessments of the campaigns that were examined demonstrate that the recorded percentages of poor quality water ranged from 40% to 90% while the percentages of good quality water varied from 7.7% to 54.5%. The remaining samples reveal different classes with varying percentages. Most of the sites in all campaigns had drinking water parameters that exceeded the values established by the World Health Organization and Moroccan standards. Nevertheless, the parameters of Temperature, pH, TH, DO, Ca2+, SO42-, K+, NH4+, and bacteriological parameters were within the required limits. The results of the assessment based on electrical conductivity suggest a significant increase in salinity levels, with an average of 2744.75 µS/cm in 2000, and 2957.84 µS/cm in 2021. The findings of the study reveal a positive assessment regarding the quality of the water samples examined during the eight sampling campaigns, as indicated by the PI and KR indices. However, additional investigation of the SAR, Na%, and MH indices revealed that three water samples acquired from separate surveys are not appropriate for irrigation purposes, showing that groundwater must be controlled until it can be properly used. The outcomes accentuate the necessity of consistent monitoring and evaluation of water quality parameters to establish the safe and sustainable exploitation of water resources for domestic and agricultural purposes. Elevated salinity levels in Quaternary aquifers resulting from natural mechanisms such as increased rates of evaporation and geological factors may have contributed to the degradation of groundwater quality.